Orbital forcing of the East Antarctic ice sheet during the Pliocene and Early Pleistocene - Patterson, Molly O.; McKay, R.; Naish, T.; Escutia, C.; Jimenez-Espejo, F. J.; Raymo, M. E.; Meyers, S. R.; Tauxe, L.; Brinkhuis, H.; Pross, Jörg (Nature geoscience, 2014)
The Pliocene and Early Pleistocene, between 5.3 and 0.8 million years ago, span a transition from a global climate state that was 2-3 °C warmer than present with limited ice sheets in the Northern Hemisphere to one that was characterized by continental-scale glaciations at both poles. Growth and decay of these ice sheets was paced by variations in the Earth’s orbit around the Sun. However, the nature of the influence of orbital forcing on the ice sheets is unclear, particularly in light of the absence of a strong 20,000-year precession signal in geologic records of global ice volume and sea level. Here we present a record of the rate of accumulation of iceberg-rafted debris offshore from the East Antarctic ice sheet, adjacent to the Wilkes Subglacial Basin, between 4.3 and 2.2 million years ago. We infer that maximum iceberg debris accumulation is associated with the enhanced calving of icebergs during ice-sheet margin retreat. In the warmer part of the record, between 4.3 and 3.5 million years ago, spectral analyses show a dominant periodicity of about 40,000 years. Subsequently, the powers of the 100,000-year and 20,000-year signals strengthen. We suggest that, as the Southern Ocean cooled between 3.5 and 2.5 million years ago, the development of a perennial sea-ice field limited the oceanic forcing of the ice sheet. After this threshold was crossed, substantial retreat of the East Antarctic ice sheet occurred only during austral summer insolation maxima, as controlled by the precession cycle.